The Liver as a Target Organ for Gene Therapy: State of the Art, Challenges, and Future Perspectives - Frank Jacobs; Stephanie C. Gordts; Ilayaraja Muthuramu; Bart De Geest (MDPI AG, 2012)
The liver is a target for gene therapy of inborn errors of metabolism, of hemophilia, and of acquired diseases such as liver cancer and hepatitis. The ideal gene transfer strategy should deliver the transgene DNA to parenchymal liver cells with accuracy and precision in the absence of side effects. Liver sinusoids are highly specialized capillaries with a particular endothelial lining: the endothelium contains open fenestrae, whereas a basal lamina is lacking. Fenestrae provide a direct access of gene transfer vectors to the space of Disse, in which numerous microvilli from parenchymal liver cells protrude. The small diameter of fenestrae in humans constitutes an anatomical barrier for most gene transfer vectors with the exception of adeno-associated viral (AAV) vectors. Recent studies have demonstrated the superiority of novel AAV serotypes for hepatocyte-directed gene transfer applications based on enhanced transduction, reduced prevalence of neutralizing antibodies, and diminished capsid immune responses. In a landmark clinical trial, hemophilia B was successfully treated with an AAV8 human factor IX expressing vector. Notwithstanding significant progress, clinical experience with these technologies remains very limited and many unanswered questions warrant further study. Therefore, the field should continue to progress as it has over the past decade, cautiously and diligently.